The ethics and politics of breastfeeding : power, pleasure, poetics - Lee, Robyn (University of Toronto Press, 2018)
"Responding to the most widely read breastfeeding manual, La Leche League's The Womanly Art of Breastfeeding, Robyn Lee's The Ethics and Politics of Breastfeeding explores breastfeeding as an art that must be developed through skillful application of effort and distinguished from a merely natural or physiological process. The Ethics and Politics of Breastfeeding challenges the dominant understanding of breastfeeding and cultivates an alternative conception as an ethical, embodied practice of the self. Drawing on the work of Michel Foucault, Emmanuel Levinas, and Luce Irigaray, Lee develops a new understanding of breastfeeding as an "art of living," where the practice is reconsidered in the light of ongoing social inequalities."--